ROLE OF CORTICOTROPHIN RELEASING HORMONE IN DETERMINING THE LENGTH OF GESTATION: PLACENTAL CLOCK - Ansari, Asmat Kamal; Memon, Salma Farrukh; Qureshi, Aijaz (Pakistan Journal of Physiology, 2011)
Background: CRH is a hormone of stress and its secretion is greatly increased during pregnancy especially in the last trimester. During pregnancy it is also secreted by the placenta and plays role in determining the length of gestation and initiation of parturition. Methods: This prospective study was carried out in the Department of Physiology, and clinical laboratory of Isra University Hyderabad. Fifty cases of normal, singleton, uterine pregnancy were selected in their 31–34 weeks of gestation. Blood sample was taken and level of CRH was determined by Elisa method. The subjects were followed till delivery and length of gestation noted. Results: Mean length of gestation in all subjects was 41.85±1.80 weeks. Mean plasma CRH in all subjects was 50.02±9.33 ηg/ml. When length of gestation was measured according to CRH values by dividing the subjects in four groups, it was found that length of gestation decreased significantly as CRH increased. Length of gestation revealed a negative correlation with CRH values with an r value of -0.901. Conclusion: CRH level in normal pregnancy has negative correlation with length of gestation.